Developing instructional materials of English morphology for English department college-learners - Chothibul Umam (Universitas Islam Negeri Palangka Raya, Indonesia, 2015)
The role of knowledge on English Morphology for the students of English Language Education (henceforth ELE) cannot be neglected. However, the preliminary observations done by the researcher during the instructional process of English Morphology at the State College for Islamic Studies (STAIN) Kediri Indonesia, for three academic years shows that most of the students still get difficulty in understanding the course content.